Distribution of Tick Haemaphysalis punctata (Acari, Ixodidae) in Ukraine - Akimov, I.A.; Nebogatkin, I.V. (Вестник зоологии, 2012)
The northern boundary of H. punctata range was studied. This boundary of its native range (where this species is common and its mass reproductions are periodically recorded) was found to go through Odesa, Mykolaiv, Kherson, Zaporizhia, Donetsk and Lugansk oblasts. Clarified that the boundary of its temporary range (where this species occurs periodically and is dependent on human factors totally) was clarified to go through Volyn, Rivne, Zhytomyr, Kyiv, Chernihiv and Sumy regions. The range of H. punctata is fully subjected to anthropogenic factors in areas where this species dwelt in historically recent times only, and in ancestral areas of distribution such factors affects only dynamics and indices of abundance.